Protestantismus und Areligiosität: ein Forschungsdesiderat - Barth, Hans-Martin (Kerygma und Dogma, 2016)
The most secularized areas in Europe are those territories originally shaped by the Reformation. How is this to be explained? Is it for historical reasons (such as the Thirty Years' War or the GDR Regime)? Or is it due to theological deficits in Lutheran theology (such as a lack of ecclesiological interest or the exclusiveness of the "sola" formulas)? What is the challenge for Protestantism resulting from an analysis of these problems? How can the message of the Reformation once again relate to contemporary sensibilities and connect with the pluralistic world? Is the tradition of so-called Free Protestantism able to point out a successful path? Should secular faith become the model of future Christendom? Both analysis and therapy badly need further investigation.